PENGARUH MOTIVASI KERJA DAN KEDISIPLINAN TERHADAP KINERJA GURU SMA ASSALAAM SURAKARTA DENGAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI VARIABEL MODERASI - Malik, Abdul -; Sriwidodo, Untung - (Universitas Slamet Riyadi, 2013)
This research is purpose to analyze impact of work motivation to teachers work in Senior High School of Assalaam Surakarta, analyze impact of discipline to teachers performance in Senior High School of Assalam Surakarta, analyze impact of headmaster leadership to teachers work in Senior High School of Assalaam Surakarta, analyze impact of work motivation that moderated of headmaster leadership to teachers performance in Senior High School of Assalaam Surakarta, analyze impact of discipline that moderated of headmaster leadership to teachers performance in Senior High School of Assalaam Surakarta. Population of this research are 55 teachers in Senior High School of Assalaam Surakarta. Sampling technique used census method. Collecting data technique used questioners by validity and reliability test. The analyze data used double linier regression and absolute difference test. Result of this research showed: first hypothesis coefficient significant of work motivation variable is 0,145, so motivation variable is not have significant impact to teachers performance. Second hypothesis coefficient significant of discipline variable is 0,372, so discipline variable is not have significant impact to teachers performance. Third hypothesis coefficient significant of headmaster leadership variable is 0,075, so headmaster leadership variable is not have significant impact to teachers performance. So headmaster leadership is not moderated work motivation to teachers performance and headmaster leadership is not moderated discipline to teachers performance. Result of determination regression test showed that R2 0,310, so impact value of work motivation and discipline variable to teachers performance with headmaster leadership as moderate variable is 31 percent, more than it is influenced the others variable. Keywords: work motivation, discipline, headmaster leadership, teachers performance